Squamous metaplasia of lactiferous ducts (SMOLD): an under-recognised entity. Issue 12 (9th December 2020) - Ofri, Adam; Dona, Eddy; O'Toole, Sandra
Abstract : Breast abscesses are a common surgical problem, typically occurring secondary to lactation mastitis. Recurrent subareolar abscesses are rarely reported and may be poorly recognised as a presentation of squamous metaplasia of lactiferous ducts, known eponymously as 'Zuska's disease'. Other synonyms include subareolar breast abscess and lactiferous or mammary fistulas. Recognition of this painful entity is crucial for optimal outcomes since typical breast abscess management of recurrent aspiration or incision and drainage can lead to recurrence and chronic complications, such as fistula formation.